THE IMPACT OF HUMAN RESOURCES QUALITY ON WORK ACHIEVEMENT IN PUBLIC SERVICES (Case Study in Ngalukoja Village, Ende Regency) - Arifin, Hadjrah (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This study aims to determine the impact of the quality of human resources on work performance in providing public services in the village of Ngalukoja, Ende Regency. The methods used are reference studies, field observations, and interviews. The research results were analyzed by descriptive qualitative. The quality of human resources has a very large impact on work performance in providing public services to the community. The results showed that most of the Ngalukoja village employees had an average high school education level, while only one person had a bachelor’s qualification. The low quality of human resources results in low quality work performance in providing public services to the community that is not maximized. The low quality of human resources can be seen from the competency aspect in mastering information skills and computer technology, which is still low and the facilities they have are still very limited.